Potensi Batang Pisang sebagai Media Filter pada Pengolahan Air Limbah Laundry - Saragih, Guntar Marolop; Kalsum, Siti Umi; Sari, Tri Wulan (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Banana stems have the potential to be used as filter media in the laundry wastewater treatment process. Laundry wastewater will contain hazardous substances that have the potential to pollute the environment if it is not treated adequately before disposal. Considering the fact that banana stems have a high hygroscopic capacity and cellulose content which is capable of absorbing inorganic chemicals, the use of banana stems as a filter media is considered a realistic option. The research method used is the filtration reactor method, and there are differences in the amount of time invested and the thickness of the banana stem, which can range from 20 to 40 centimeters. There were differences in the decrease in the parameter values of pH, COD, TSS, phosphate, and MBAS with variations in the thickness of the banana stem media. The largest decrease in pH observed occurred at a media thickness of 40 centimeters. Based on the research results, it was found that there was variation in the extent to which parameters were reduced overall. A one-day soak is the most effective way to reduce the severity of these properties. In addition, research findings show that banana stems are not effective enough in processing laundry wastewater.